Single-faceted IrO2 monolayer enabling high-performing proton exchange membrane water electrolysis beyond 10,000 h stability at 1.5 A cm-2 - Yang, Deren; Zhang, Chunyang; Qin, Yufeng; Yue, Yang; Liu, Yubo; Shi, Xiaoyun; Hua, Kang; An, Xuemin; Jin, Louyu; Zhang, Yipeng; Zuo, Shouwei; Tan, Aidong; et al. (Nature communications, 2025)
Both commercial and laboratory-synthesized IrO 2 catalysts typically possess rutile-type structures with multiple facets. Theoretical results predict the (101) facet is the most energetically favorable for oxygen evolution reaction owing to its lowest energy barrier. Achieving monolayer thickness while exposing this desired facet is a significant opportunity for IrO 2 . Herein, we develop an ammonia-induced facet engineering for the synthesis of single-faceted IrO 2 (101) monolayer. It achieves 230 mV overpotential at 10 mA cm geo -2 in a three-electrode system and 1.70 V at 2 A cm geo -2 in a proton exchange membrane (PEM) electrolyzer. Though facet engineering primarily contributes to modulating the intrinsic activity rather than stability, single-faceted IrO 2 monolayer performs over 10,000-hour stability at constant 1.5 A cm geo -2 (3.95 mV kh -1 decay) and 1000-hour stability at 0.2 mg Ir cm geo -2 under fluctuating conditions. This work proposes that ammonia-induced facet engineering of IrO 2 monolayer enables facet-dependent oxygen evolution reaction (OER) performance and high stability in industrial-scale PEM electrolysis. IrO2 catalysts typically feature rutile structures with multiple facets. The authors develop an ammonia-induced method to synthesize single-faceted CuO₂ monolayers with the theoretically optimal (101) facet, resulting in high oxygen evolution activity and stability (>10,000 h) in a water electrolyser.